Faktor-Faktor yang Memengaruhi Kepuasan Kerja Perawat Ruang Rawat Inap: Factors Affecting Job Satisfaction Among Inpatient Ward Nurses - Nindi Lathifatul Mar’ah; Yeni Rusyani Rusyani; Rizal Fajri; Lia Fadlilah (Jurnal Keperawatan Berbudaya Sehat, 2026)
Nurse job satisfaction is an essential indicator of healthcare quality influenced by various organizational factors. This study aimed to analyze the factors influencing the job satisfaction of inpatient ward nurses at RSU Nurusyifa Kudus. This quantitative correlational study with a cross-sectional approach was conducted from October to December 2025. The sample consisted of 43 inpatient nurses selected via total sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression. The results showed that the majority of respondents were aged >31 years (65.1%), female (74.4%), held a Bachelor of Nursing (Ners) degree (62.8%), and felt moderately satisfied (48.8%). Simultaneously, compensation, interpersonal relationships, leadership style, and work motivation significantly affected job satisfaction ( ; ). Partially, compensation ( ) and interpersonal relationships ( ) had significant effects, whereas leadership style ( ) and work motivation ( ) had no significant effects. In conclusion, compensation and interpersonal relationships are the dominant factors influencing nurse job satisfaction. Hospital management is advised to evaluate the compensation system and maintain a harmonious working climate to enhance nurses' job satisfaction.